The Leoncino Dwarf Galaxy: Exploring the Low-metallicity End of the Luminosity–Metallicity and Mass–Metallicity Relations - McQuinn, Kristen. B. W.; Berg, Danielle A.; Skillman, Evan D.; Adams, Elizabeth A. K.; Cannon, John M.; Dolphin, Andrew E.; Salzer, John J.; Giovanelli, Riccardo; Haynes, Martha P.; Hirschauer, Alec S.; Janoweicki, Steven; Klapkowski, Myles; et al. (The Astrophysical journal, 2020)
Extremely metal-poor (XMP) galaxies are low-mass, star-forming galaxies with gas-phase oxygen abundances below 12 + log(O/H) = 7.35 ( Z ). Galaxy evolution scenarios suggest three pathways to form an XMP: (1) secular evolution at low galaxy masses, (2) slow evolution in voids, or (3) dilution of measured abundances from infall of pristine gas. The recently discovered XMP galaxy Leoncino, with an oxygen abundance below 3% Z , provides an opportunity to explore these different scenarios. Using Hubble Space Telescope imaging of the resolved stellar populations of Leoncino, we measure the distance to the galaxy to be Mpc and find that Leoncino is located in an underdense environment. Leoncino has a compact morphology, hosts a population of young, massive stars, has a high gas-to-star mass ratio, and shows signs of interaction with a galaxy nearby on the sky, UGC 5186. Similar to nearly all XMP galaxies known in the nearby universe, Leoncino is offset from the Luminosity–Metallicity (LZ) relation. However, Leoncino is consistent with the stellar Mass–Metallicity (MZ) relation defined by Local Volume galaxies. Thus, our results suggest that the offset from the LZ relation is due to higher recent star formation, likely triggered by a minor interaction, while the low oxygen abundance is consistent with the expectation that low-mass galaxies will undergo secular evolution marked by inefficient star formation and metal loss via galactic winds. This is in contrast to XMP galaxies that are outliers in both the LZ and MZ relations; in such cases, the low oxygen abundances are best explained by dilution due to the infall of pristine gas. We also discuss why quiescent XMP galaxies are underrepresented in current surveys.